Multiple Positive Solutions of a Singular Emden-Fowler Type Problem for Second-Order Impulsive Differential Systems. (10th August 2010) - Lee, Eun Kyoung; Lee, Yong-Hoon
Abstract : This paper studies the existence, and multiplicity of positive solutions of a singular boundary value problem for second-order differential systems with impulse effects. By using the upper and lower solutions method and fixed point index arguments, criteria of the multiplicity, existence and nonexistence of positive solutions with respect to parameters given in the system are established.